Investigating the potential of ammonium retention by graphene oxide ceramic nanofiltration membranes for the treatment of semiconductor wastewater. (January 2022) - Cha, Minju; Boo, Chanhee; Song, In-Hyuck; Park, Chanhyuk
Abstract: Ceramic membranes with high chemical and fouling resistance can play a critical role in treating industrial wastewater. In the present study, we demonstrate the fabrication of graphene oxide (GO) assembled ceramic nanofiltration (NF) membranes that provide effective ammonium retention and excellent fouling resistance for treating semiconductor wastewater. The GO-ceramic NF membranes were prepared via a layer-by-layer (LbL) assembly of GO and polyethyleneimine (PEI) on a ceramic ultrafiltration (UF) substrate. The successful fabrication of the GO-ceramic NF membranes was verified through surface characterization and pore size evaluation. We also investigated the performance of GO-ceramic NF membranes assembled with different numbers of bilayers for the rejection of ammonium ions. GO-ceramic NF membranes with three GO-PEI bilayers exhibited 8.4- and 3.2-times higher ammonium removal with simulated and real semiconductor wastewater, respectively, compared to the pristine ceramic UF substrate. We also assessed flux recovery after filtration using real semiconductor wastewater samples to validate the lower fouling potential of the GO-ceramic NF membranes. Results indicate that flux recovery increases from 39.1 % in the pristine UF substrate to 71.0 % and 90.8 % for the three- and ten-bilayers GO-ceramic NF membranes, respectively. The low-fouling GO-ceramic NF membranes developed in this study are effective and promising options for the removal of ammonium ions from semiconductor wastewater. Graphical abstract: Image 1 Highlights: Ceramic NF membranes were fabricated using an LbL assembly with GO and PEI. Ammonium retention improved after coating of three or more GO-PEI bilayers. Flux recovery experiments showed lower fouling potential for fabricated membrane. Ten GO-PEI bilayers had an optimal effect on ammonium retention and antifouling.